Neuroma embryonic sympathetic - Neuroblastoma. Review of the literature - Agnieszka Budny; Jakub Litak; Cezary Grochowski (Kazimierz Wielki University, 2017)
Embryonic Neuroma sympathetic is derived from nerve cells, of which during normal development are sympathetic ganglia and the adrenal Medulla. Primary outbreak is found for this reason along the axis of the body - in the pelvis, retroperitoneal, bone, liver, neck, back of the cranial cavity or in the adrenal glands. In the form of congenital disease may refer to both of the adrenal glands.